Obscene images in the cycle Moscow Taverns and the problems connected with translating them into Polish - Borkowska, Kaja (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The article reviews the role of obscene vocabulary in Sergei Yesenin’s cycle Moscow Taverns, as well as the problems connected with rendering them into Polish. The material ofthe analysis, Yeseninʼs poetry, is famous for a high frequency of terms of abuse. The resultsof the examination make it possible to pinpoint certain regularities in translation transformations.The potential translation variants are shown on basis of three Polish translators’works, pertaining to different periods. Due to this, it is possible to observe the evolving attitudesto translating obscene images in Yesenin’s poetry in a diachronic perspective.